1993
DOI: 10.1002/jso.2930540412
|View full text |Cite
|
Sign up to set email alerts
|

Study of c‐erbB‐2 protein and epidermal growth factor receptor expression and DNA ploidy pattern in colorectal carcinoma

Abstract: Correlation of c-erbB-2 protein (n = 44), epidermal growth factor receptor (EGFR) (n = 41) expression, and DNA ploidy pattern (n = 42) with clinical outcomes of human colorectal cancers was studied. Using monoclonal antibodies against c-erbB-2 protein and EGFR, an immunohistochemical study of the expression of c-erbB-2 protein and EGFR in frozen tissue sections from the lesion was performed. There was no significant correlation between the expression of c-erbB-2 protein and clinicopathological findings such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 22 publications
0
8
0
1
Order By: Relevance
“…Besides gene amplification, several investigators have described the involvement of ETS family (Scott et al, 2000) and AP-2 family (Bates and Hurst, 1997) transcription factors in the gene overexpression. ERBB2 overexpression has also been reported in cancers of colon (Nakae et al, 1993;Kapitanovic et al, 1994;Maurer et al, 1998), prostate (Ross et al, 1993;Morote et al, 1999), ovary (Fajac et al, 1995) and pancreatic (Yamanaka et al, 1993) origin. However, the mechanisms leading to increased expression of the gene have not been investigated in these tumours.…”
Section: Discussionmentioning
confidence: 92%
“…Besides gene amplification, several investigators have described the involvement of ETS family (Scott et al, 2000) and AP-2 family (Bates and Hurst, 1997) transcription factors in the gene overexpression. ERBB2 overexpression has also been reported in cancers of colon (Nakae et al, 1993;Kapitanovic et al, 1994;Maurer et al, 1998), prostate (Ross et al, 1993;Morote et al, 1999), ovary (Fajac et al, 1995) and pancreatic (Yamanaka et al, 1993) origin. However, the mechanisms leading to increased expression of the gene have not been investigated in these tumours.…”
Section: Discussionmentioning
confidence: 92%
“…Previous IHC studies examining HER-2 expression reported different percentages of positive cells, ranging from 0 to 100%. [16][17][18][19][20][21][22][23][24] The major cause of these discrepancies seems to be the different criteria for evaluating the results. Studies that scored intracytoplasmic staining as positive reported larger frequencies, whereas studies that reported only membrane staining as positive was scored lower or zero frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Constitutive tyrosine activation of h-catenin (24,25) and several protein tyrosine kinases, such as c-Kit (26), c-erbB2 (27), c-Met (28), and pp60(c-Src) (29)(30)(31)(32), is frequently observed in premalignant colorectal lesions. It was also reported that an antisense-mediated down-regulation of pp60(c-Src) expression severely decreased tumorigenicity of HT29 colon adenocarcinoma cells (33), although potential transcriptional targets of pp60(c-Src) still remained elusive.…”
Section: Introductionmentioning
confidence: 99%